THE INFLUENCE OF PROFITABILITY, FINANCIAL LEVERAGE AND FREE CASH INFLOW ON CATERING DIVIDENDS AMONG MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE DURING 2017-2020 PERIOD - Adiputra, I Gede; Ruslim, Herman (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this study was to examine the effect of profitability, financial leverage, and free cash inflow on the catering tip dividend in manufacturing companies listed on the BEI. The research time span is from 2017-2020. By using EViews 11, the results show that “profitability has a positive and significant effect” on dividend premium, Influence has a negative and significant effect on premium dividends, and free cash inflow has a positive effect on premium dividends in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2020 period.